Utility of pharmacists on clinical outcomes of patients in palliative care: A short review - Brkić Jovana; Tasić Ljiljana; Krajnović Dušanka (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Pharmacists as the most accessible health care professionals in outpatient settings can improve palliative patient care. The aim of this review was to assess utility of pharmacists (the effectiveness of pharmacists' interventions) on clinical outcomes of patients in palliative care at all levels of health care and in home care. Two electronic databases were searched: PubMed and SCOPUS (last searched August 2014). Primary studies, of any type of research design, in English, related to clinical outcomes of patients in palliative care and pharmacists' interventions were eligible. Studies that used surrogate outcome measures, such as number of pharmacists' recommendations were excluded. A total of 764 reports were found, and only three of them met our inclusion criteria. All of them assessed effects of pharmacists' interventions in outpatient settings and were case series. Symptoms improvement and stabilization of patients' conditions has been the main utility of pharmacists' interventions. Assessed quality of two studies was moderate, and one study had low quality. As number of studies and quality of the evidence were limited, and results of reviewed studies indicate that pharmacists' interventions potentially could improve clinical outcomes of patients in palliative care, more research is needed to provide evidences in this field.